2007
DOI: 10.1038/sj.npp.1301336
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Metabolites Level in CSF is Related to the 5-HTT Gene Polymorphism in Treatment-Resistant Depression

Abstract: The serotonin (5-hydroxytryptamine) transporter (5-HTT) is considered to affect the pathogenesis of mood disorders. Large number of genetic association studies between 5-HTT functional polymorphisms and vulnerability of mood disorders and therapeutic response to antidepressants has been carried out. We investigated the influence of 5-HTT-linked polymorphic region (5-HTTLPR) and 5-HTT 17 bp variable number of tandem repeat polymorphism (5-HTTVNTR) polymorphisms on concentrations of monoamine metabolites in cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
(39 reference statements)
2
9
0
1
Order By: Relevance
“…Our finding of elevated internal jugular 5-HIAA overflow in depressed patients carrying the s allele of the 5-HTT gene is in agreement with the recent findings by Kishida and colleagues, 62 who observed elevated 5-HIAA levels in the CSF of patients with MDD carrying the s allele. While it has been observed that 5-HTT expression and serotonin uptake are impaired with the presence of the short-form haplotype, 21,30 studies in postmortem brain tissue demonstrated no relationship between 5-HTT binding potential and genotype in suicide victims.…”
Section: Commentsupporting
confidence: 82%
“…Our finding of elevated internal jugular 5-HIAA overflow in depressed patients carrying the s allele of the 5-HTT gene is in agreement with the recent findings by Kishida and colleagues, 62 who observed elevated 5-HIAA levels in the CSF of patients with MDD carrying the s allele. While it has been observed that 5-HTT expression and serotonin uptake are impaired with the presence of the short-form haplotype, 21,30 studies in postmortem brain tissue demonstrated no relationship between 5-HTT binding potential and genotype in suicide victims.…”
Section: Commentsupporting
confidence: 82%
“…Examples for minisatellite loci include two distinct VNTRs in the serotonin transporter gene (5-HTT, also SLC6A4) which have been linked to phenotype in a variety of populations: HTTLPR, a 20–23 bp TR in the promoter, which occurs as 14 copies and 16 copies, and STin2, a 17 bp TR in the second intron, which occurs as 9, 10 and 12 copies. HTTLPR variants have been associated with depression (10), bipolar disorder (11), symptoms of Alzheimer's disease (12) and may act through a decrease in transcriptional activity of the gene in patients with the shorter allele (13). STin2 has been associated with schizophrenia (14), depression (15), symptoms of Alzheimer's disease (12,16) and treatment outcome in alcohol dependent patients (17).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the long 5-HTTLPR allele was associated with the melancholic subtype of major depression and the short 5-HTTLPR allele with AD [49,50]. From the current patient sample with persistent mood disorders, we previously reported no significant influence of the 5HTTLPR on CSF-HVA but a tendency on CSF 5-HIAA (P = 0.06) [51]. However, in the subset of patients with the major depressive disorder, the CSF 5-HIAA and HVA concentrations were significantly higher in short-allele carriers than in nonshort-allele carriers of the 5-HTTLPR [51].…”
Section: Discussionmentioning
confidence: 50%
“…From the current patient sample with persistent mood disorders, we previously reported no significant influence of the 5HTTLPR on CSF-HVA but a tendency on CSF 5-HIAA (P = 0.06) [51]. However, in the subset of patients with the major depressive disorder, the CSF 5-HIAA and HVA concentrations were significantly higher in short-allele carriers than in nonshort-allele carriers of the 5-HTTLPR [51]. In this study, we found no significant effect of 5HTTLPR with susceptibility to AD.…”
Section: Discussionmentioning
confidence: 73%